2012
DOI: 10.1016/j.jamda.2011.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Multilevel Intervention to Improve Outcomes of Residents in Nursing Homes in Need of Improvement

Abstract: Purpose A comprehensive multilevel intervention was tested to build organizational capacity to create and sustain improvement in quality of care and subsequently improve resident outcomes in nursing homes in need of improvement. Intervention facilities (n=29) received a two-year multilevel intervention with monthly on-site consultation from expert nurses with graduate education in gerontological nursing. Attention control facilities (n=29) that also needed to improve resident outcomes received monthly informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 75 publications
2
63
0
2
Order By: Relevance
“…The fact that we saw these behaviors at least intermittently in every NH suggests that existing capacity is present in NHs and it that can be more widely developed. Rantz et al [38] came to a similar conclusion in their quality improvement intervention which improved outcomes such as pressure ulcers and weight loss without adding staffing or costs. Our findings are supported by other prior work suggesting that improving organizational capacity has to do with seemingly “ordinary activities” [39], p. 384 that are embedded in social structures that “make use of real-time information, simultaneously explore multiple alternatives, [and] rely on quickly created new knowledge….” [40], p. 919, to facilitate the ability of staff to continuously create solutions to emerging problems.…”
Section: Resultsmentioning
confidence: 87%
“…The fact that we saw these behaviors at least intermittently in every NH suggests that existing capacity is present in NHs and it that can be more widely developed. Rantz et al [38] came to a similar conclusion in their quality improvement intervention which improved outcomes such as pressure ulcers and weight loss without adding staffing or costs. Our findings are supported by other prior work suggesting that improving organizational capacity has to do with seemingly “ordinary activities” [39], p. 384 that are embedded in social structures that “make use of real-time information, simultaneously explore multiple alternatives, [and] rely on quickly created new knowledge….” [40], p. 919, to facilitate the ability of staff to continuously create solutions to emerging problems.…”
Section: Resultsmentioning
confidence: 87%
“…Participants were deemed responsive to mealtime assistance based on a gain of 15 % or more in meal intake based on a previous research [2,18]. Table 2 displays the primary intervention components, which were consistent with those necessary for an effective translational research effort (see "Introduction") [1,3,[7][8][9]. Staff training activities were conducted at the unit level and included all scheduled nurse aides and supervisory nurses (e.g., unit charge nurse) on each of the seven units for all three shifts (day, evening, and night).…”
Section: Original Researchmentioning
confidence: 99%
“…Unfortunately, despite this growing evidence base, efforts to translate efficacious clinical interventions into LTC practice have had limited success [3][4][5][6]. However, research has identified several key issues important to address to facilitate the successful translation of care quality improvements into LTC practice [1,3,[7][8][9]. First, multiple levels of staff should be involved in training-namely, licensed nurses in a supervisory role and nurse aides responsible for direct care [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…These interventions have comprised the following: MDTs providing an integrated care approach, 13 more skilled RAC staff for assessment/recognition of illness, 9,13,16,17 education and clinical coaching, 13,18 improved care coordination by, for example nurse practitioners, better assessment of acute/subacute changes in condition, 14 nutritional screening/intervention, 19 advance care planning, 20 and medication review. 21 It was based on these studies that we developed the ARCHUS intervention.…”
Section: Discussionmentioning
confidence: 99%